2019
DOI: 10.1016/j.jbiomech.2019.109338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foot orthoses on dynamic balance and basketball free-throw accuracy before and after physical fatigue

Abstract: Effects of foot orthoses on dynamic balance and basketball free-Effects of foot orthoses on dynamic balance and basketball free-throw accuracy Effects of foot orthoses on dynamic balance and basketball free-throw accuracy before and after physical fatigue before and after physical fatigue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In the process of basketball skill jump shot, the athlete's body is likely to tilt and be imbalanced. Only under the guarantee of coordinated force between the core area and the foot arch can the trunk be firmly supported and the upper limbs can effectively carry out coordinated shooting movements [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of basketball skill jump shot, the athlete's body is likely to tilt and be imbalanced. Only under the guarantee of coordinated force between the core area and the foot arch can the trunk be firmly supported and the upper limbs can effectively carry out coordinated shooting movements [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to optimize the training process in terms of postural stability to be as efficient as possible and to avoid possible injury and chronic pain syndromes [ 29 , 30 ]. It is essential to understand the risk factors such as an abnormal foot alignment for athletes who perform high-intensity power training before devising proper custom foot orthoses and further research is needed to improve the clinical outcomes of athletes who suffer injury due to an impaired balance [ 31 , 32 , 33 , 34 ]. Statistical results obtained by the methodology developed encourage the further development of the proposed approach.…”
Section: Discussionmentioning
confidence: 99%
“…12 This contrasts to other insole studies, which indicated significant contributions in physical benefits including lower energy cost and better dynamic and static balances. 8,26 The possible explanation would be due to the complexity of the stop-jump task, which includes the complex movements of stop-braking (horizontal) and jump take-off (vertical) phases in a maximum effort. The movements tested in other studies are relatively simple and low intensity such as standing balance and walking.…”
Section: Discussionmentioning
confidence: 99%